2007
DOI: 10.1016/j.snb.2007.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Application of carbon nano-powders for a gas micro-preconcentrator

Abstract: This paper presents a feasibility study on the development of a gas preconcentrator based on micro-reactor technology on silicon. The objectives are to select a gas adsorbent material, to produce a silicon micro-reactor with an integrated heater, and finally to introduce the most suitable adsorbent into the micro-channels of the device. Preliminary results related to the characterization of a carbon adsorbent for the development of a device for the preconcentration of benzene are reported. Carbon nano-powders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 30 publications
0
32
0
1
Order By: Relevance
“…The different channels are designed with the necessity of having some pillars or walls within the channels in order to control the powders deposition by fluidic solutions [23,24] . The neutral microchannel is designed without structures in the internal chamber while the zigzag design with channel system at inlet/outlet, mostly used in this work, is made with "V" shaped structures in order to improve the flow distribution not only during the adsorbent deposition but also during experiments.…”
Section: Preconcentratormentioning
confidence: 99%
See 2 more Smart Citations
“…The different channels are designed with the necessity of having some pillars or walls within the channels in order to control the powders deposition by fluidic solutions [23,24] . The neutral microchannel is designed without structures in the internal chamber while the zigzag design with channel system at inlet/outlet, mostly used in this work, is made with "V" shaped structures in order to improve the flow distribution not only during the adsorbent deposition but also during experiments.…”
Section: Preconcentratormentioning
confidence: 99%
“…[24] These experiments on the fluidic deposition of the adsorbent have shown that the presence of pillars in the preconcentration chamber, particularly in the "zigzag" design, is a key factor to homogenize the distribution of the liquid flow through the entire device and to enhance the carbon deposition. It was observed that the use of porous silicon has increased the quantity of deposited carbon in the micro-channels.…”
Section: Adsorbent Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to have an autonomous component, for either the thermal treatments of the adsorbent materials and the desorption of the trapped gases, a platinum heater is integrated on the backside of the device by screen printing and the electrical connections are made with gold wires pasted on a platinum lacquer. This heating element is used to heat the device at temperatures up to 500 °C with a very homogeneous distribution of the temperature considering the good thermal conductivity of the silicon, as it was reported in our previous works [1,2].…”
Section: Preconcentrator Fabricationmentioning
confidence: 99%
“…In a previous study [1,2], a gas pre-concentrator based on porous silicon micro-channels filled with carbon nanopowders from a fluidic solution has been developed. The present work aims to improve the performances of this device, with new approaches in the design as well as in the choice of adsorbent materials and modes of operation.…”
Section: Introductionmentioning
confidence: 99%